Protist taxonomic and functional diversity in aquatic ecosystems of the Brazilian Atlantic Forest - Carvalho da Silva, Vanessa; Fernandes, Noemi (PeerJ, 2023)
The Brazilian Atlantic Forest and its associated ecosystems are highly biodiverse but still understudied, especially with respect to eukaryotic microbes. Protists represent the largest proportion of eukaryotic diversity and play important roles in nutrient cycling and maintenance of the ecosystems in which they occur. However, much of protist diversity remains unknown, particularly in the Neotropics. Understanding the taxonomic and functional diversity of these organisms is urgently needed, not only to fill this gap in our knowledge, but also to enable the development of public policies for biological conservation. This is the first study to investigate the taxonomic and trophic diversity of the major protist groups in freshwater systems and brackish coastal lagoons located in fragments of the Brazilian Atlantic Forest by DNA metabarcoding, using high-throughput sequencing of the gene coding for the V4 region of the 18S rRNA gene. We compared α and β diversity for all protist communities and assessed the relative abundance of phototrophic, consumer, and parasitic taxa. We found that the protist communities of coastal lagoons are as diverse as the freshwater systems studied in terms of α diversity, although differed significantly in terms of taxonomic composition. Our results still showed a notable functional homogeneity between the trophic groups in freshwater environments. Beta diversity was higher among freshwater samples, suggesting a greater level of heterogeneity within this group of samples concerning the composition and abundance of OTUs.Ciliophora was the most represented group in freshwater, while Diatomea dominated diversity in coastal lagoons.
Keywords: Coastal lagoons; DNA metabarcoding; Eukaryotic diversity; Inland ecosystems; Neotropics; South America; Protist diversity